Effectiveness of the Sub-district Public Report Service Action (ALLAMAK) in the Context of Optimizing Public Services in Alam Barajo Sub-district, Jambi City - Fajar Danuwarta; Nofi Nurman; Yudi Armansyah; Aliyas; Yunita Elianda (STMIK Indonesia Banda Aceh, 2026)
This study aims to analyze the effectiveness of the digital service of the Sub-district Public Report Service Action (ALLAMAK) at the Alam Barajo Sub-district Office, Jambi City. The study used qualitative methods with interview, observation, and documentation techniques. The analysis refers to William N. Dunn's Public Policy Evaluation theory which emphasizes effectiveness, efficiency, responsiveness, accuracy, and relevance of impact as indicators of public policy performance (Dunn, 2018). The results show that the ALLAMAK service has met public service standards according to Permenpan-RB Number 14 of 2017, particularly in the aspects of transparency, accountability, and ease of service access (Government of Indonesia, 2017). Although generally considered effective, obstacles were still found in ease of use, speed of response, and a decrease in public satisfaction levels. The main driving factors for service effectiveness come from the implementation of the Electronic-Based Government System policy and the increasing public demand for digital public services (OECD, 2020), while the main obstacles include limited technological literacy and internet access (UNDP, 2019). Therefore, improving facilities, infrastructure, and community readiness is still needed to optimize ALLAMAK services.